Modified alkaloid pattern in developing tobacco callus - Tiburcio, A F (Plant science : an international journal of experimental plant biology, 1985)
Developing Nicotiana tabacum L. cv. Wisconsin-38 callus grown on modified Murashige-Skoog (MS) medium with Kao organic acids (pyruvic, citric, malic and fumaric acids) contains abnormally high levels of nornicotine and total alkaloids when compared with the leaves of the donor plant. Nornicotine/nicotine ratios observed during callus development suggest that nicotine is converted into nornicotine in the callus, with subsequent movement of alkaloids into roots formed on the callus and into the agar medium. Addition of Kao organic acids to the medium increases alkaloid levels, but cannot account for the abnormal increase in nicotine demethylation. This study thus reports two new findings: (a) that the total alkaloid content of tobacco callus can be greatly enhanced to 3.75% on a dry weight basis by exogenous organic acids, and (b) that endogenous nornicotine can accumulate in tobacco tissue cultures